Fiscal risk sharing and redistribution between Austrian states - Lukas Reiss (Austrian Institute of Economic Research (WIFO), 2021)
This study analyses the extent of fiscal risk sharing and redistribution for Austria from 2000 to 2019. Overall, fiscal policy smooths about one tenth of regional GDP shocks. While this is primarily driven by the federal budget and social security funds, there is also a significant contribution of the revenue sharing scheme between the federal government and subnational governments. Most interestingly, the case of the Austrian revenue sharing system shows that there are intergovernmental transfer schemes which achieve risk sharing without much redistribution. This is due to mechanisms within this system which grant high-income states shares in federal revenue which are higher than their respective population shares. Furthermore, due to other mechanisms, the Austrian fiscal system is overall highly redistributive between states, but net contributions vary substantially over time.
Keywords: R10; R50; H77; 330; Risk sharing; fiscal federalism; regional accounts